(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2017)
We deal with the interrogation of an accused person in criminal proceedings, objectively defining it and the controversy over its legal nature, and then we argue that the accused person himself can waive it, whether he is present or absent at the hearing, because judicial interrogation is an essential means of self-defense and in light of the constitutional right to silence.